Coding complexity in the human motor circuit - Heinrichs‐Graham, Elizabeth (Hum Brain Mapp, 2015)
Cortical oscillatory dynamics are known to be critical for human movement, although their functional significance remains unclear. In particular, there is a strong beta (15–30 Hz) desynchronization that begins before movement onset and continues during movement, before rebounding after movement termination. Several studies have connected this response to motor planning and/or movement selection operations, but to date such studies have examined only the early aspects of the response (i.e., before movement) and a limited number of parameters. In this study, we used magnetoencephalography (MEG) and a novel motor sequence paradigm to probe how motor plan complexity modulates peri‐movement beta oscillations, and connectivity within activated circuits. We also examined the dynamics by imaging beta activity before and during movement execution and extracting virtual sensors from key regions. We found stronger beta desynchronization during complex relative to simple sequences in the right parietal and left dorsolateral prefrontal cortex (DLPFC) during movement execution. There was also an increase in functional connectivity between the left DLPFC and right parietal shortly after movement onset during complex but not simple sequences, which produced a significant conditional effect (i.e., complex > simple) that was not attributable to differences in response amplitude. This study is the first to demonstrate that complexity modulates the dynamics of the peri‐movement beta ERD, which provides crucial new data on the functional role of this well‐known oscillatory motor response. These data further suggest that execution of complex motor behavior may recruit key regions of the fronto‐parietal network, in addition to traditional sensorimotor regions. Hum Brain Mapp 36:5155–5167, 2015. © 2015 Wiley Periodicals, Inc.